2004
DOI: 10.1002/jcp.20087
|View full text |Cite
|
Sign up to set email alerts
|

Multiple signaling conduits regulate global differentiation‐specific gene expression in PC12 cells

Abstract: PC12 cells serve as a model for exploring nerve growth factor (NGF)-stimulated signal pathways that mediate neural differentiation. We previously demonstrated that neurofilament light chain (NFLC) gene induction by NGF requires collaborative extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) signaling. Herein, we investigate the broader requirement for integrated ERK and JNK signaling in NGF-stimulated gene expression. NGF stimulates differentiation as well as maintenance of cell via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 49 publications
4
51
0
Order By: Relevance
“…The activation of Ret by GDNF results in the activation of the MAP kinase pathways (van Weering & Bos 1997). Specifically, Ret activates the ERK and JNK signaling pathways (Marek et al 2004, Asai et al 2006. Our results showed that GDNF induced ERK, p38, JNK, and Akt phosphorylation in human colon cancer cells.…”
Section: Discussionmentioning
confidence: 54%
“…The activation of Ret by GDNF results in the activation of the MAP kinase pathways (van Weering & Bos 1997). Specifically, Ret activates the ERK and JNK signaling pathways (Marek et al 2004, Asai et al 2006. Our results showed that GDNF induced ERK, p38, JNK, and Akt phosphorylation in human colon cancer cells.…”
Section: Discussionmentioning
confidence: 54%
“…In the first place, all genes that are up-or down-regulated by NGF in these studies are also up-or down-regulated in our study. Secondly, genes with a particularly strong response to NGF [Dusp6, Egr1, matrix metallopeptidase 3 (Mmp3), and Npy; FCs of at least over 10], also showed a relatively strong response in other studies that assessed expression of many genes at once (Angelastro et al 2000;Marek et al 2004;Lee et al 2005). Moreover, among these 20 genes are Dusp6, TGFb1, Mmp3, s100a4, Egr1, and Fosl1, which are reported to be regulated by NGF and not by insulin-like growth factor (Marek et al 2004).…”
Section: Validation Of Microarray Datamentioning
confidence: 99%
“…Secondly, genes with a particularly strong response to NGF [Dusp6, Egr1, matrix metallopeptidase 3 (Mmp3), and Npy; FCs of at least over 10], also showed a relatively strong response in other studies that assessed expression of many genes at once (Angelastro et al 2000;Marek et al 2004;Lee et al 2005). Moreover, among these 20 genes are Dusp6, TGFb1, Mmp3, s100a4, Egr1, and Fosl1, which are reported to be regulated by NGF and not by insulin-like growth factor (Marek et al 2004). The latter growth factor provides trophic support to PC12 cells only, indicating that the identified genes in our study are specifically regulated during NGF-induced neuronal differentiation (Marek et al 2004).…”
Section: Validation Of Microarray Datamentioning
confidence: 99%
See 2 more Smart Citations